2016
DOI: 10.1021/acs.jpca.6b06685
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Photolysis in Salty Snow

Abstract: Nitrate photolysis from snow can have a significant impact on the oxidative capacity of the local atmosphere, but the factors affecting the release of gas-phase products are not well understood. Here, we report a systematic study of the amounts of NO, NO, and total nitrogen oxides (NOy) emitted from illuminated snow samples as a function of both nitrate and total salt (NaCl and Instant Ocean) concentration. The results provide experimental evidence that the release of nitrogen oxides to the gas phase is direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…However, the question of whether such effects might change the partitioning of nitrate within a frozen matrix has not been addressed. As we suggested recently, a difference in the partitioning of nitrate in salty frozen matrices could significantly change the local atmospheric oxidation environment in polar regions influenced by sea ice.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, the question of whether such effects might change the partitioning of nitrate within a frozen matrix has not been addressed. As we suggested recently, a difference in the partitioning of nitrate in salty frozen matrices could significantly change the local atmospheric oxidation environment in polar regions influenced by sea ice.…”
Section: Introductionmentioning
confidence: 72%
“…However, very recently we have reported that the additional presence of halide salts at environmentally relevant concentrations can drastically alter this correlation . The amount of gas-phase nitrogen oxide production generally decreases with an increase in the prefreezing concentration of added halide salt, consistent with a dilution of the nitrate concentration in the liquid-like surface region due to an increased brine volume.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…94 Highly variable quantum yields of nitrate photolysis on ice and snow are reported because they are strongly inuenced by the location of nitrate anions in an ice grain, 95,96 and the co-existing species (e.g., Cl À ). 97 Meusinger et al have proposed two photochemical domains of nitrate photolysis: photolabile nitrate anion and nitrate anion buried within the ice grain. 95 Photoproducts produced from photolabile nitrate anion can escape the ice grain and hence the quantum yields are higher than those of nitrate anion buried within the ice grain.…”
Section: Ice and Snowmentioning
confidence: 99%
“…Water ice contains liquid inclusions and liquid-filled grain boundaries, which may trap reagents within them. Solutes excluded from the ice crystal during a slow freezing process also create a concentrated solution at the air–ice interface, which can lead to altered reaction mechanisms. Moreover, recent work has shown that the distribution of excluded molecules in the quasi-liquid layer at the ice surface is not always uniform but that solutes may be arranged in uneven patches and self-associate, with liquid or frozen regions between them. Thus, reagents may either be solvated or exist in solid form at the ice surface, even in the case of highly soluble species like nitrate; this inhomogeneous distribution may play a crucial role in the reaction dynamics at the surface.…”
Section: Introductionmentioning
confidence: 99%